A little learning is a dangerous thing? The ethics of teaching accidental tourists in higher education - McDonald, F.; Howell, Jennifer; Lewis, B. (AARE, 2013)
This paper raises questions about the ethical issues that arise for academics and universities when under-graduate students enrol in classes outside of their discipline - classes that are not designed to be multi-disciplinary or introductory. We term these students ‘accidental tourists’. Differences between disciplines in terms of pedagogy, norms, language and understanding may pose challenges for accidental tourists in achieving desired learning outcomes. This paper begins a discussion about whether lecturers and universities have any ethical obligations towards supporting the learning of these students. This examination illustrates the challenges faced by lecturers some of whom, we theorise, may experience a form of moral distress facing a conflict between personal beliefs and organisational requirements. It also critically examines the role and responsibilities of universities towards students and towards their staff. This paper indicates the need for greater reflection about this issue, especially given the many constraints facing lecturers and universities.